A New Approach for Angle-Selective Slabs: Theory and Design - Liu, Jiawei; Liao, Shaowei; Xiu, Xin; Yan, Mengzhu; Xue, Quan; Che, Wenquan (IEEE transactions on microwave theory and techniques, 2025)
A new approach for angle-selective slabs (ASSlabs) is proposed in this article. This approach employs an elliptic-function lowpass prototype (ELP) to achieve the characteristics of low-profile and high angular selectivity of ASSlabs. First, the ideal ELP mapping into the angular domain is demonstrated. Then, a realizable ELP based on a slotline-backed split-ring resonator (SRR) is proposed, with its elements optimized by the ideal ELP using a genetic algorithm. The parameters mapping between the unit cell and the equivalent circuit model (ECM) is constructed subsequently. Next, third-order and fifth-order ASSlabs with elliptic-function lowpass responses in the angular domain are designed. The third-order ASSlab is fabricated and measured to validate the correctness and synthesizability of the approach. The measured results show a roll-off rate of 0.50 dB/° in the transition band at the observed frequency of 6 GHz with a profile of only 0.16λ _{o} , and great frequency consistency is witnessed in the range from 5.6 to 6.4 GHz with a fraction bandwidth (FBW) of 16.7%. In addition, an enlarged roll-off rate of 1.16 dB/° is revealed by the simulated results of the fifth-order ASSlab with a profile of 0.28λ _{o} , illustrating the superiority of the proposed approach in designing low-profile ASSlabs with high angular selectivity.